Edukasi Manfaat Pangan Lokal untuk Peningkatan Produksi ASI Ibu Menyusui di PMB Yustati Ambarita Muaro Jambi - Suci Rahmani Nurita; Tuhu Perwitasari (Jurnal Abdimas Kesehatan (JAK), 2023)
The achievement of exclusive breastfeeding in Jambi province in 2020 reached 59.9%. This number has not met the target of exclusive breastfeeding set nationally by the government, which is 80% of the number of babies in Indonesia. One of the contributing factors is the less breast milk syndrome. Insufficient breastfeeding syndrome can be treated with improvements in lactation management and consuming food sources that can affect the work of the hormone prolactin in producing breast milk. Food sources based on local wisdom that have been extensively studied for their effect on breast milk production include katuk leaves, moringa leaf extract, papaya leaves and fruit, banana heart, and mung bean extract. The purpose of carrying out this educational activity is a change in knowledge and a healthier attitude. The education carried out targets an increase in the knowledge and attitudes of the education participants with the output in the form of educational media, activity results reports and journal publications. Community Service Activities will be held on July 30 2022 starting with an opening (introduction, time contract, explanation of objectives and materials to be provided and distribution of pre-test questionnaires), followed by educating participants about local foods that can increase breast milk production and ending with closing ( distribution of leaflets, distribution of post-test questionnaires, and closing greetings). This activity was attended by approximately 15 participants at PMB Yustati Ambarita. The results of the evaluation during the educational process were that the participants seemed enthusiastic about the counseling material, the participants listened to the counseling carefully and the participants asked questions related to the material that was not clear. The results of the analysis of the pre and post test questionnaires on 10 participants, there was an increase in the participants' knowledge and attitudes from before the educational activity and after the educational activity. It is hoped that breastfeeding mothers can implement the knowledge gained in order to increase milk production by consuming local food that is around the community